2015
DOI: 10.1002/pc.23748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the different hydrophobic groups of polycarboxylate superplasticizers on the properties in cement mortars

Abstract: Four novel polycarboxylate superplasticizers (PCEs) with different hydrophobic groups incorporating acrylic acid (AA) and polyether (PEO) macromonomers (C4‐M‐1, C5‐M‐2, C6‐M‐3, and C11‐M‐4) as repeating unit were synthesized by the free radical polymerization. Characterization of the molecular structures of the PCEs by Gel permeation chromatography (GPC), Nuclear Magnetic Resonance (1H NMR), Fourier‐transform infrared (FT‐IR), and Thermogravimetric analyses (TGA) were performed. After meticulous studying on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Since came out in the 1980s, polycarboxylate superplasticizers (PCE) have been increasingly used in cement and concrete industry, such as buildings, bridges and dams fields . Traditional PCE polymers are composed of polyethylene main chain, poly (ethylene glycol) branch chain and carboxylic side groups, and it's convenient to achieve diverse functions and specially solve some problems in concrete engineering because their chemical structure has the potential to be modified . As an important type of concrete admixture, the main function of superplasticizers is to increase the dispersion of cement paste,, leading to a low water‐to‐cement ratio (w/c) and high strength concrete.…”
Section: Methodsmentioning
confidence: 99%
“…Since came out in the 1980s, polycarboxylate superplasticizers (PCE) have been increasingly used in cement and concrete industry, such as buildings, bridges and dams fields . Traditional PCE polymers are composed of polyethylene main chain, poly (ethylene glycol) branch chain and carboxylic side groups, and it's convenient to achieve diverse functions and specially solve some problems in concrete engineering because their chemical structure has the potential to be modified . As an important type of concrete admixture, the main function of superplasticizers is to increase the dispersion of cement paste,, leading to a low water‐to‐cement ratio (w/c) and high strength concrete.…”
Section: Methodsmentioning
confidence: 99%
“…A total organic carbon (TOC) analyzer (Multi N/C3100, Analytikjene AG, Germany) was used to measure the TOC content of the SPs that were not adsorbed in the solution. Then the amount of crosslinked SPs adsorbed was computed on the basic of the difference between the residual amount and the initial amount 23 . The samples were prepared according to the method of the report 24 .…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Then the amount of crosslinked SPs adsorbed was computed on the basic of the difference between the residual amount and the initial amount. 23 The samples were prepared according to the method of the report. 24 Crosslinked SPs (0.2% of cement weight) were added into the cement slurries with water cement ratio of 4.…”
Section: Performance Measurements 241 | Fluidity Of Cement Slurriesmentioning
confidence: 99%
“…Results show that the zeta potential behavior can reflect the adsorption mechanism of surfactants onto solid particles. Meanwhile, in situ attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy was introduced in a recent study of a cementitious system as a surface-sensitive technique that can provide mechanistic information on adsorption [ 31 , 32 , 33 , 34 ]. Via spectroscopic study, the structure–property relationship of the surfactant and cement phase is revealed, and some adsorption models can be established.…”
Section: Introductionmentioning
confidence: 99%